TINJAUAN TENTANG HUBUNGAN TENTANG KEHENDAK TUHAN DENGAN KEADILAN TUHAN - Sariah Sariah (TOLERANSI: Media Ilmiah Komunikasi Umat Beragama, 2009)
Writing trying to see the differences of human power over the will and actions that lead to acts of the will of the absolute faham and justice of God in the flow - the flow of Islamic Theology. How do tbe will of God according to their absolute, whether absolute or God's will is not to say absolute. whether it can be said fairly, that God punishes those who do wrong rather than on his own and vice versa if God did not punish people so, whether the will of God is absolute